Spectrometric evaluation of biotransformed agro-industrial residues and their humic substances by UV–visible and infrared spectroscopy and their effect on winter wheat productivity - Juliana Moisés; Juan Manuel Martinez; Gastón Iocoli; Matías Duval; Juan Galantini (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Agro-industrial residues could be bio transformed to improve crop production and reduce environmental risk. Application of humic substances (HS) extracted from residues could be an alternative fertilization strategy. The objectives were i) to characterize different bio transformed agro-industrial residues (BR) and their HS by combining UV-vis and FT-IR techniques, and ii) to assess the effects of their application on wheat crop development and production.Method Two experiments were performed with winter wheat. The residues used were sunflower shells biotransformed by Pleurotus ostreatus fungus, alperujo naturally biotransformed by microorganisms in the environment and solid municipal waste biotransformed by Californian worms and composting. The HS were extracted from these residues. A pot experiment was performed with solid residue incorporated into the soil (Petrocalcic Haplustoll) using four nitrogen (N) levels calculated as the equivalent amount of N considering the amount of organic N (0, 50, 100 and 150 kg N ha-1). A Petri dish experiment was performed to evaluate the effect of an application of HS extracted from each BR on early wheat development.Results In general, application of BR produced a negative crop response regardless of the residue and rate. The IR spectra of three BR showed similar absorption zones but with different intensities.Conclusion The application of BR in terms of the type of residue and rate had variable, mostly negative, effects on the wheat crop. However, extraction of HS from the BR and the subsequent application favored crop development. Spectrometric techniques, such as UV-Visible and FT-IR, are useful to verify the potential effect of HS as biostimulants of plant growth.